Monitoring the Shear Fatigue Response of Reinforced Concrete Beams Subjected to Moving Loads using Digital Image Correlation - Benny Suryanto; George Staniforth (Institute of Research and Community Outreach - Petra Christian University, 2019)
A series of three reinforced concrete beams without shear reinforcement were tested to failure under a centre-span monotonic load, a centre-span pulsating load, and a stepwise-moving pulsating load. During each experiment, load-deflection response was continuously monitored and at several stages during the experiment, the load was briefly stopped for crack observations. In addition to this manual crack mapping, more detailed crack mappings were undertaken using the digital image correlation (DIC) technique, employing the open-source DIC software Ncorr. It was shown that while the three beams exhibited a similar mode of failure (i.e. shear), each beam displayed a rather distinctive overall behaviour, particularly with regard to the load-deflection response and the nature of crack initiation and propagation. Results from the DIC analysis are presented to provide direct evidence on the damage progression during the load cycles and discuss the reduced fatigue life exhibited by the beam subjected to stepwise-moving pulsating load